PENGEMBANGAN ALAT KEPEKAAN TERHADAP HUMOR - Nida UI Hasanat; - Subandi (Jurnal Psikologi, 1998)
Humor is not only important in everyday life. but it is also potential for therapy. Humor allows people to take a distance from their problems. to see the problem from a different perspective and to reduce anxiety and helplesness. The purpose of this study was to develop a sense of humor scale which assess one's ability to perceive humor from cartoons.